Introducing hydrogen fuel cell vehicles in Malaysia - Ambrose A.F.; Rasiah R.; Al-Amin A.Q.; Chen Z. (Routledge, 2023)
adaptation; conceptual framework; consumption behavior; energy policy; fuel cell; hydrogen; mitigation; Malaysia